P. Thomas: I See Things Differently: A First Look at Autism - Kuvish (Journal of Autism and Developmental Disorders, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.sed

The print exposure of teacher candidates in relation to their achievement and self-ratings of early reading experiences - Spear-Swerling, Louise; Wei, Yan; Dostal, Hannah; Hernandez, Brittney (Reading and Writing, 2020)
This study examined the print exposure of teacher candidates (N = 195) in relation to their GPAs, achievement in reading and writing on the SAT, and their self-ratings of their own early (K to Grade 5) reading experiences. Participants came from undergraduate and Masters programs in varied certification areas and from two different universities. Print exposure measures included author recognition tests for both fiction and nonfiction; a questionnaire about participants’ current voluntary reading habits for books, magazines, newspapers, and digital print media; and favorite authors/books questions. Exploratory factor analysis suggested four factors underlying the different print exposure measures: (1) fiction book reading volume; (2) current magazine and newspaper reading; (3) nonfiction book reading volume and (4) current book reading habits for enjoyment. Only fiction and nonfiction book reading volume related positively to participants’ achievement, in writing as well as reading, and to their early reading experience ratings. A subgroup of participants who had taken a specific reading methods course involving structured language content, and who had positive early reading experience self-ratings, had higher performance in the course than did participants with mixed or negative self-ratings, although the two groups did not differ in overall GPA. Findings support the view that different measures of print exposure tap somewhat different aspects of print exposure, with differing relationships to varied indicators of achievement. Results also support concerns about the reading volume and print exposure of some teacher candidates. © 2020, Springer Nature B.V.
2 citations (Crossref) [2023-10-31] WOS:000563131900009
Keywords: Print exposure; Reading; Reading habits; Teacher candidates; Teacher preparation; Writing; dept.sed; peer-reviewed

Transdisciplinary Approach Practicum for Speech-Language Pathology and Special Education Graduate Students - Weiss, Deborah; Cook, Barbara; Eren, Ruth (Journal of Autism and Developmental Disorders, 2020)
Speech-language pathology and special education graduate student teams participated in an intensive summer practicum for social communication skills with children with autism spectrum disorders, utilizing a transdisciplinary approach that aligned to the frameworks utilized for implementation science. Questionnaires measuring transdisciplinary approach knowledge and comfort level were administered pre/post-practicum. Results of the questionnaires, written daily team reflections, course evaluations, and a focus group interview indicated an increase in all measures, including an increased knowledge of TA, increased understanding and comfort level with the other discipline, and a higher level of confidence and openness in working collaboratively utilizing a transdisciplinary approach. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
12 citations (Crossref) [2023-10-31] WOS:000516272800002
Keywords: Academic Performance; Article; Autism Spectrum Disorder; Autism spectrum disorder; Child; Collaborative teaming; Communication; Education; Special; Female; Humans; Implementation science; Interdisciplinary Research; Interprofessional collaboration; Male; Special education; Speech-Language Pathology; Speech-language pathology; Students; Health Occupations; Surveys and Questionnaires; Transdisciplinary; academic achievement; autism; child; comfort; communication skill; course evaluation; dept.cmd; dept.sed; education; female; graduate student; health student; human; implementation science; interdisciplinary education; interdisciplinary research; interpersonal communication; interview; knowledge; male; peer-reviewed; pretest posttest design; priority journal; procedures; professional development; psychology; quantitative analysis; questionnaire; social competence; special education; speech disorder; teacher; training

Core dimensions of autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L.J. (New Oxford Textbook of Psychiatry, 2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that manifests during the early developmental period of childhood. Behaviourally characterized by impairments in social interaction and communication, in combination with stereotyped and restricted patterns of behaviour and/or interest, it is currently believed that ASD occurs in approximately 1–2% of individuals. ASD is more prevalent among males than females (4–5:1), but the mechanisms resulting in this discrepancy are still unclear. This chapter will serve as an introduction to ASD, covering the topics of disorder history, prevalence rates, demographics, diagnostic criteria, differential diagnosis, and discussions on current and future diagnostic classification systems. The remaining chapters within Section 4 will then provide detailed discussions on more specific topics related to ASD, including current understandings of treatment planning, prevention and epidemiology, genetics, imaging, and disorder management.
tex.ids: volkmarCoreDimensionsAutism2020a
Keywords: dept.sed